Implementation of E-Modules in Improving Students' Competence, Interest, and Motivation in Haircutting Learning for Grade XI Graduates of SMKN Surabaya - Qonita, Anggi Mara; Pratiwi, Ursila Indah; Usodoningtyas, Sri; Pramesti, Khofifah Indar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine the effect of the implementation of an Android application-based e-module on improving students' learning outcomes in cognitive and psychomotor aspects, as well as on their interest and motivation in learning about hairdressing graduation techniques at SMKN Surabaya. The background of this study is based on the low learning outcomes, interest, and motivation of students in participating in hairdressing practical learning. This study uses a Pre-Experimental Design method with a One-Group Pretest-Posttest Design model. The study population includes all 105 students of grade XI Beauty Treatment at SMKN 8 Surabaya, with 33 students of grade XI KC 2 as samples determined using purposive sampling. The research instrument consists of a multiple-choice test to measure cognitive learning outcomes and a questionnaire to assess interest and motivation in learning. Data were analyzed through validity, reliability, difficulty level, discrimination power, normality test, and paired sample t-test. The results showed a significant increase in learning outcomes, with an average cognitive score of 88.9 and psychomotor score of 91.5. The t-test yielded a value of 14,446 with a significance of 0.000, which means there is a significant difference before and after the use of the e-module. In addition, students' learning interest reached 95% and learning motivation 88%, both of which are classified as very good. The conclusion is that the implementation of the Android-based e-module is effective in improving cognitive and psychomotor learning outcomes, while also being able to foster students' interest and motivation in learning. This e-module is recommended as an alternative innovative learning media that supports practical learning in vocational schools, especially in the competency of graduation technical haircutting.